Diseño hidráulico del sistema de drenaje pluvial urbano de la ciudad de Calzada - Noriega Dávila, José Luis (2002)
Population growth occurred in the majority of cities in the country during the past years, has resulted in the increase of the demand for greater and better public services, among which of particular importance the surplus of aguás storm; known as urban stormwater drainage. It project of thesis called: DESIGN hydraulic OF THE SYSTEM OF DRAINAGE RAIN URBAN OF THE CITY OF BOOTED, seeks to give solution integral to them serious problems of floods and waterlogging, that is produce in the city of booted; When are ordinary and extraordinary pluvial precipitations. In the present thesis work, has been surveying the current urban area (87.16 has) and in the area of future expansion (70.62 has), as well as an area for industrial zone (16.60 has) making a total of 174.38 Ha., information that allowed us to get the drawings of the project; also done with a projection of 2 urban planning...